Α case of late diagnosis of compound heterozygosity for Hb Adana (HBA2:c.179G>A) in trans to an α+- thalassemia deletion: guilty or innocent - Tampaki, A (Hippokratia, 2020)
Background: Hemoglobin Adana is a non-deletional alpha chain mutation, particularly rare, and to date, it is mostly described in coinheritance to other a-thalassemia mutations. Such interactions result in various phenotypes depending on the underlying genotype. Since routine hematological tests do not detect the aforementioned unstable variant, it is quite likely a diagnosis to be missed or delayed, with any complications this may have for a patient. Description of the case: A case report of late mutation identification in a 64-year-old woman of Greek origin is described. The importance of conducting not only molecular studies to confirm common mutations, such as the –a3.7 kb deletion, but also DNA studies in patients whose phenotype and results of standard tests are not consistent or who present with severe, late complications is highlighted. Conclusion: The awareness of the necessity for accurate diagnosis is raised, especially in populations that thalassemia prevails and is attributed to numerous mutations. HIPPOKRATIA 2020, 24(1): 38-42.